3D game engine architecture : engineering real-time applications with Wild Magic - Eberly, David H. (Morgan Kaufmann series in interactive 3D technology., 2005)
Dave Eberly's 3D Game Engine Design was the first professional guide to the essential concepts and algorithms of real-time 3D engines and quickly became a classic of game development. Dave's new book 3D Game Engine Architecture continues the tradition with a comprehensive look at the software engineering and programming of 3D engines. This book is a complete guide to the engineering process, starting with a walk-through of the graphics pipeline showing how to construct the core elements of 3D systems, including data structures, the math system, and the object system. Dave explains how to manage data with scene graphs, how to build rendering and camera systems, and how to handle level of detail, terrain, and animation. Advanced rendering effects such as vertex and pixel shaders are also covered as well as collision detection and physics systems. The book concludes with a discussion of application design, development tools, and coding standards for the source code of the new version of the Wild Magic engine included on the CD-ROM. Wild Magic is a commercial-quality game engine used by many companies and is a unique resource for the game development community. *CD-ROM with the complete C++ source code for Wild Magic version 3, a commercial-quality game engine for Windows, Linux, and OS X. *A comprehensive, practical guide to all the steps necessary to build professional-quality real-time simulations with just minimal mathematics required. *Emphasizes the application of software engineering principles and describes the architecture of large libraries.